TINJAUAN LITERATUR: PENYEMPURNAAN PROSES PENEMPAAN LOGAM DENGAN ANALISIS TEGANGAN DAN TEMPERATUR - Ibnu Rosyid Ridwana; Fakhrurriza; Boy Arya Sadewa; Ratna Aulia Puspita Sari; Zalfa Arridwan; Sri Hastuti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Variations in billet temperature often lead to uneven stress and heat distribution on the dies during closed-die hot forging. This review aims to identify the die regions that are most vulnerable to excessive loading and to examine how thermal conditions influence the quality of the forged product. The literature analyzed includes studies that combine finite element simulations with actual forging trials carried out at different heating temperatures. The findings consistently show that the die edges experience the highest stress concentrations, particularly when forging is performed at lower billet temperatures, which increases the likelihood of local plastic deformation. In contrast, temperatures within the optimal range promote smoother metal flow, more complete die filling, and a longer die service life. Overall, this review highlights the crucial role of proper billet temperature control in maintaining dimensional accuracy and ensuring stable forging performance.